Origen and Plato on the Superiority and Perfection of the Soul - Zhimeng Lin (Religions)
Origen’s theology is fundamentally rooted in the question of whether he upheld the pre-existence of the soul or focused more on the soul’s superiority over the body and its perfection. While inheriting many ideas from Plato, Origen adapted them in accordance with Christian doctrine. Both Origen and Plato emphasized that the soul governs the body and is superior to it in both status and importance. The image of God resides in human soul, not the body, guiding individuals toward the perfection of the soul and the attainment of the whole virtues. Origen’s tripartite distinction of spirit, soul, and body is intrinsically connected to Plato’s tripartite theory of the soul, with the intermediary of the incarnate soul corresponding to the ambiguous role of thumos (spiritedness) in Plato’s dialogue. This suggests that humans are capable of both good and evil, a potential grounded in free will rather than the sin of the body. Nevertheless, Origen assigned the body a more important role, asserting that the Incarnation not only depended on the body but also facilitated the practice of virtue, positioning the body as central to his theory of resurrection. Origen also adopted Plato’s epistemology, teleology of knowledge, and theory of participation. He emphasized that the perfection of the soul requires liberation from the dominance of the senses, using Plato’s dialectical method and drawing inspiration from the Holy Spirit to achieve comprehensive knowledge and spiritual maturity. Origen should not be viewed as merely a Platonist or an anti-Platonist. Both he and Plato shared concerns about the correct way of life and perfect knowledge, and both sought to bridge the gap between the majority and the minority, avoiding both elitism and populism.